Estudo epidemiológico das vítimas de acidentes de trânsito admitidas em hospital de emergência de Fortaleza - Peixoto, Maria das Graças Barbosa (1998)
In recent years external causes of death (traffic accidents, violence) have been growing progressively in Brazil, becoming a major public health problem. In Ceará, traffic accidents have been increasing, reaching a frightening share of overall mortality. In 1996, traffic accidents had become the leading single cause of mortality in the group external causes with 32.0% of deaths, being the same in the State of Ceará as in the capital city. The objective of this study was to analyze epidemiological aspects in a population of traffic accident victims admitted to the biggest emergency hospital in Fortaleza, Institute José Frota (IJF). The case histories of patients admitted in consequence of traffic accidents are described, the study being conducted during hospitalization in the period from February to April 1997 (n=377). It was found that 8% of the patients studied died, while 89.9% survived without any physical handicap and 2.1% with physical impairment. The most frequent traumatism was the fracture of the cranium, which accounted 46.9% of the injured. Among the victims who died, the biggest part died as a result of brain injuries, 50% of those who suffered from remaining physical impairment had medullar injuries. The percentage of the permanently handicapped among victims was 2.1%. Analyzing the type of accident, collisions, run overs and knock downs play an important part, having a high case / fatality and accounting for severe traumatisms, especially in the group of young people. The major number of victims was found in the age group between 15 and 49 years - 71% of the total injured. Accident victims are predominately male, 81%, being the gender ratio 4:1. The majority of the victims were motorcyclists (26%), followed by pedestrians 21.5%. Analyzing the causes of the accidents, it was observed that carelessness of the driver was the most frequent (49%), followed by negligence of the victim (46%) and excess of velocity (42.8%). It was also verified that the first aid for the victims was done by passersby and that 66% of the hospitalized patients received clinical surgery treatment.